ANTIMUTAGENIC POTENTIAL OF POLLEN GRAINS OF SOME MEDICINAL PLANT SPECIES - Kaur, Rajwant; Nagpal, Avinash Kaur; Katnoria, Jatinder Kaur (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study was planned to explore the antimutagenic response of ethanolic extracts of pollen grains of four plant species viz., Bauhinia variegata, Cassia biflora, Cassia glauca and Cassia siamea belonging to Fabaceae family. Methods: Ames assay was used to evaluate the antimuatagenic activity of the ethanolic extracts of pollen grains of four plant species. Both TA 98 and TA 100 strains of Salmonella typhimurium were used in presence and absence of S9 mix during the present study. Results: Among four species studied, pollen extracts of Bauhinia variegata and Cassia biflora had shown maximum percentage inhibition of revertant colonies during presence and absence of S9 mix, respectively. Conclusion: The present study reveals that pollen extract of four plant species viz., Bauhinia variegata, Cassia glauca, Cassia biflora and Cassia siamea exhibited antimutagenic potential against two direct acting mutagens viz., (4 nitro-o-phenylenediamine; NPD for TA 98 and sodium azide for TA 100) and one indirect acting mutagen (2 amino-flourine; 2AF) which indicates that pollen grains of these species can act as potential source of anticancer drugs. Keywords: Ames assay, Bauhinia variegata, Pharmaceutical, Cancer